2022
DOI: 10.1007/s00348-022-03395-9
|View full text |Cite
|
Sign up to set email alerts
|

Transitional shockwave/boundary layer interaction experiments in the R2Ch blowdown wind tunnel

Abstract: Transitional Shockwave/Boundary Layer Interactions (SBLI) is studied experimentally. Experiments are conducted on a hollow-cylinder flare model in the R2Ch blowdown facility at a Mach number of 5 for three different Reynolds numbers in the transitional regime. Unsteady wall pressure measurements are conducted along with mean and unsteady heat flux measurements and high-speed Schlieren imaging. The images are then processed using Proper Orthogonal Decomposition (POD) and Spectral Proper Orthogonal Decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Benay et al (2006) performed an experimental study of a Mach 5 hollow-cylinder/flare flow and observed periodic and steady streamwise streaks near flow reattachment using surface oil-flow visualization with various Reynolds numbers. As a continuation, similar experiments were recently performed by Lugrin et al (2022) at Mach 5 with three different Reynolds numbers. They observed streamwise streaks with different wavenumbers near reattachment and oblique modes travelling in the shear layer above the recirculation zone using a spectral proper orthogonal decomposition of surface infrared and high-speed schlieren images.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Benay et al (2006) performed an experimental study of a Mach 5 hollow-cylinder/flare flow and observed periodic and steady streamwise streaks near flow reattachment using surface oil-flow visualization with various Reynolds numbers. As a continuation, similar experiments were recently performed by Lugrin et al (2022) at Mach 5 with three different Reynolds numbers. They observed streamwise streaks with different wavenumbers near reattachment and oblique modes travelling in the shear layer above the recirculation zone using a spectral proper orthogonal decomposition of surface infrared and high-speed schlieren images.…”
Section: Introductionmentioning
confidence: 77%
“…As a continuation, similar experiments were recently performed by Lugrin et al . (2022) at Mach 5 with three different Reynolds numbers. They observed streamwise streaks with different wavenumbers near reattachment and oblique modes travelling in the shear layer above the recirculation zone using a spectral proper orthogonal decomposition of surface infrared and high-speed schlieren images.…”
Section: Introductionmentioning
confidence: 99%
“…This choice is supported by the fact that second Mack modes exhibit strong pressure fluctuations close to the wall, as shown by the optimal response profiles in figure 3(g). Also, that kind of sensor is commonly used in supersonic experimental studies (Lugrin et al 2022).…”
Section: Selecting Actuator and Sensorsmentioning
confidence: 99%
“…The next year, Lugrin et al. (2022) published their experimental findings on a hollow cylinder-flare with a sharp leading edge at the R2Ch blowdown tunnel at ONERA. Using heat transfer measurements, they observed clear streaks under the reattached boundary layer at various wavenumbers.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing spectral proper orthogonal decomposition (SPOD), they determined that transition on that geometry was caused by the linear amplification of oblique modes that interact nonlinearly, creating the streamwise striations observed frequently in experiments. The next year, Lugrin et al (2022) published their experimental findings on a hollow cylinder-flare with a sharp leading edge at the R2Ch blowdown tunnel at ONERA. Using heat transfer measurements, they observed clear streaks under the reattached boundary layer at various wavenumbers.…”
Section: Introductionmentioning
confidence: 99%